Three legacies of humanitarianism in China. (22nd July 2013) - Hirono, Miwa
Abstract : The rise of China has altered the context of the international humanitarian community of donors and aid agencies. China is becoming one of the key actors in this grouping, undertaking infrastructure projects in areas in which paramount humanitarian challenges exist. The literature discusses how the Chinese approach differs from that of Western donors, but it does not pay much attention to why China concentrates on its state‐centric and infrastructure‐based approach. This paper seeks to shed some light on this subject by examining the historical evolution of the concept of humanitarianism in China. This evolution has produced three legacies: (i) the ideal of a well‐ordered state; (ii) anti‐Western sentiment; and (iii) the notion of comprehensive development based on a human‐oriented approach. China's policies and discourses on assistance in humanitarian crises today rest on these three legacies. Traditional donors would be well advised to consider carefully the implications of the Chinese understanding of humanitarianism when engaging with the country.